Near infrared (NIR) lanthanide emissive Langmuir-Blodgett monolayers formed using Nd(III) directed self-assembly synthesis of chiral amphiphilic ligands. - Barry, D; Kitchen, J; Albrecht, M; Faulkner, S; Gunnlaugsson, T (2013)
The incorporation of chiral amphiphilic lanthanide-directed self-assembled Nd(III) complexes (Nd.13 and Nd.23) into stable Langmuir monolayers, and the subsequent Langmuir-Blodgett film formation of these, is described. The photophysical properties of the enantiomeric pair of ligands 1 and 2 in the presence of Nd(CF3SO3)3 were also investigated in CH3CN solutions using UV-vis, fluorescence, and lanthanide luminescence spectroscopies. Analysis of the resulting self-assembly processes revealed that two main species were formed in solution,1:1 and 1:3 Nd:L self-assembly complexes, with the latter being the dominant species upon the addition of 0.33 equivalents of Nd(III). Excited state lifetime measurements of Nd.13 and Nd.23 in CH3OH and CD3OD and CH3CN were also evaluated. The formation of the self-assembly in solution was also monitored by observing the changes in the circular dichroism (CD) spectra; and large differences were observed between the 1:3 and other stoichiometries in the spectra, allowing for correlation to be made with that seen in the emission studies of these systems. Surface pressure-area and surface pressure-time isotherms evidenced the formation of stable Langmuir monolayers of Nd.13 and Nd.23 at an air-water interface, and the deposition of these monolayers onto a quartz solid substrate (Langmuir-Blodgett films) gave rise to immobilized chiral monomolecular films which exhibited Nd(III) NIR luminescence upon excitation of the ligand chromophore, demonstrating efficient energy transfer to the Nd(III) excided state (sensitized) with concomitant emission centered at 800 and 1334 nm.